Evaluating How Tenure Security in Disaster Management Depends on Land Governance Based on Indonesian Case Study - Pinuji, Sukmo; de Vries , Walter Timo (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
Tenure security is a critical variable in disaster management, yet is dependent on the rules and regulations of a country with regards to land ownership and use. This study draws on three disasters that occurred in Indonesia as case studies: the tsunami in Aceh in 2004, the Sidoarjo mudflow in 2006, and the tidal flood and permanent inundation in Kabupaten Demak, reported in 1997. Using literature review approach, we compare the government responses in these examples and evaluate how they affected tenure security in each case, and presented it qualitatively. We discovered that there were different responses in terms of the declaration of a national disaster, Central Government support, the presence of a responsible agency, and how the government threatened it as a 'pure natural disaster' or a 'human-induced disaster.' We conclude that the Central Government plays an important role in ensuring tenure security during a disaster in terms of supporting laws and regulations, but the Local Government is also critical in the implementation process in land right reconstruction. Furthermore, for destroyed or lost land due to a disaster, the regulations on disaster management should distinguish between the root and cause of the disaster to ensure land rights protection and justice for the victims.